A panel of circulating miRNAs as diagnostic biomarkers for screening multiple myeloma: a systematic review and meta‐analysis. (15th November 2016) - Zhang, L.; Cao, D.; Tang, L.; Sun, C.; HU, Y.
Summary: Circulating microRNAs (miRNAs) have been proved to be effective diagnostic markers for multiple myeloma (MM). The meta‐analysis was aimed to evaluate the diagnostic value of related miRNAs. Multiple databases (PubMed, Web of Science, EMBASE, Cochrane Library, CBM, and CNKI) were systematically searched for available studies up to March 2016. All data were analyzed with the help of softwarerevman 5.3 andmetadisc 1.4. The eligible articles' quality was estimated by QUADAS‐2, and pooled parameters were acquired with the bivariate random‐effects meta‐analysis model. Subgroup analysis and meta‐regression were conducted to explore the heterogeneity of studies included. After steps of screening, seven qualified literatures were selected. They consisted of 22 studies that included 486 newly diagnosed MM patients and 292 healthy controls. Summary receiver operating characteristic (SROC) analyses of all miRNAs showed an area under the curve (AUC) of 0.86 (95%CI, 0.82–0.91). Together with the AUC, the positive likelihood ratio‐PLR 4.45 (95%CI, 3.28–6.04), negative likelihood ratio‐NLR 0.29 (95%CI, 0.24–0.35), and diagnostic odds ratio‐DOR 17.59 (95%CI, 11.26–27.4) confirmed that circulating miRNAs possessed relatively high diagnostic value in discriminating MM patients from healthy controls. For miRNAs combined together, miRNA‐1308/miRNA‐720 had the highest sensitivity 0.96 (95%CI, 0.79–1.00) and specificity 0.92 (95%CI 0.64–1.0). The subgroup and meta‐regression analyses also showed that miRNAs profiling was the sole source of heterogeneity, and the diagnostic accuracy of combined miRNAs was 6.02 times higher than single one. Combined circulating miRNAs in serum or plasma may be highly effective biomarker for diagnosis of MM.